Funerary banquets and Eupatrids: the Opferrinnen ritual in Archaic Athens - Valdés Guía, Miriam (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Attic tombs in the VII Century BC, especially in the Kerameikos, are distinguished by primary cremation and, over all, by the presence of offering trenches with banquet pottery. These elite burials show a sharp tendency to heroization which could be related with the practice of commensality and pottery destruction in the tomb.
Keywords: Tombs; VII Century B.C.; Opferrinnen; banquet; Eupatrids